UPGRADING RELIGIUSITAS, LITERASI, DAN ADAPTASI TEKNOLOGI ANAK JALANAN BERBASIS LEARNING STATION COMMUNITY - Astutik, Anita Puji; Untari, Rahmania Sri; Segara, Nuansa Bayu; Meilinda, Isna; Rahma, Aulia; Wafi, Akhmad Hasbul (Jurnal Abdimas Bina Bangsa, 2024)
The community service activities carried out are activities that aim to improve the quality of life of street children through religiosity debriefing programs, soft skill development, and digital literacy. The main focus of the activity is the development of JALITERA website, which serves as a platform for street children to access information and skills training relevant to the needs of the Times. Methods applied include observation, mapping needs, and detection of soft skills using fingerprint test, which aims to understand the potential and needs of these children. After planning the website model and socialization, activities were carried out to provide training in synergy with the materials available at JALITERA. The output of this activity is the JALITERA website and the report on the detection of soft skills of street children, which is expected to help them in developing their self-skills and improving their welfare. Thus, JALITERA is expected to be a concrete solution for street children to achieve a better future.